AKAD GANDA (HYBRID) DALAM PERSPEKTIF FIQH MUAMALAH : (Analisis Hadis) - Jureid (J-MABISYA, 2020)
The focus of this study is hybrid contract in the perspective of muamalah fiqh viewed from the hadith about bai'ataini fi ai’atin, shafqataini fi shafqatin and bay wa salaf. The type of this tresearch is a normative qualitative study (literature) with primary sources are documeints with content analysis. The prohibition of a hybrid contract is basically caused by three things; it is forbidden by religion or hîlah because it can lead to uncertainty (gharar) and obscurity (jahâlah), plunging into the practice of usury, and double contracts which lead to conflicting legal consequences on the same object. A double contract that meets sharia principles is a double contract that meets the standard or dhawabit. The certainty of contract become to big attention. The certainty between contract is something that really needs to attention. The contract in this hadith must be carried out on one contract only from several existing cases. Buying and selling and loans are two different things and different laws, so they cannot be combined into one contract. In general, both types of contracts are possible to be collected in one contract without affecting the law and its legal consequences.